2005
DOI: 10.1007/s11104-004-1994-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen in interstitial waters in the Sahel; Natural Baseline, Pollutant or Resource?

Abstract: Nitrate in the unsaturated zone between the soil surface and the water table was studied in agroforestry Parklands in north western Senegal by examination of samples obtained by hand auger. Depending on location, water tables existed at depths between 10 and 35 m below ground. Previous studies of groundwater in this region had found that large concentrations of nitrate were unconnected with anthropogenic activity. The objective of this study was to determine whether nitrogen fixing vegetation had a role in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…High NO 3 concentrations in the USZ are found widely in other arid and semi-arid areas including western United States (Walvoord et al, 2003), the Sahel in northern Africa (Edmunds and Gaye, 1997;Deans et al, 2005), the Kalahari desert in southern Africa (Heaton et al, 1983;Stone and Edmunds, 2014), Australia (Barnes et al, 1992) as well as China (Gates et al, 2008c). In these areas, as in the present study, aerobic conditions permit the inert behaviour and preservation of biogenically produced NO 3 .…”
Section: Source Of Dissolved Nitratesupporting
confidence: 69%
“…High NO 3 concentrations in the USZ are found widely in other arid and semi-arid areas including western United States (Walvoord et al, 2003), the Sahel in northern Africa (Edmunds and Gaye, 1997;Deans et al, 2005), the Kalahari desert in southern Africa (Heaton et al, 1983;Stone and Edmunds, 2014), Australia (Barnes et al, 1992) as well as China (Gates et al, 2008c). In these areas, as in the present study, aerobic conditions permit the inert behaviour and preservation of biogenically produced NO 3 .…”
Section: Source Of Dissolved Nitratesupporting
confidence: 69%
“…In contrast, some regions in the southwestern USA have very low NO 3 inventories under native vegetation, e.g., 24-76 kg N/ha, Southern High Plains, USA (McMahon et al 2006;Scanlon et al 2008). Large NO 3 reservoirs have also been found in semiarid regions in Senegal (≤ 1,000 kg N/ha), which are attributed to N fixation by native trees (Deans et al 2005). The lack of accumulation of NO 3 in soils in the Thar Desert from atmospheric deposition may be attributed to downward movement of NO 3 caused by recharge.…”
Section: Comparison With Nutrient Inventories From Previous Studiesmentioning
confidence: 99%
“…The hydrostratigraphic records trace past changes in recharge in response to variations in forcing from land-use change and climate variability (Scanlon et al , 2007aGates et al 2008;Favreau et al 2009). Unsaturated zone pore water NO 3 concentrations provide information on whether there is natural NO 3 in the profile from atmospheric deposition, as found in parts of the southwestern USA (Walvoord et al 2003), from nitrogen fixation by native vegetation, as found in Senegal (Deans et al 2005), or from mineralization and nitrification of soil organic nitrogen and over application and leaching of applied fertilizers in cropland areas (Scanlon et al 2008). Large NO 3 reservoirs in unsaturated media or in groundwater can be considered a resource for crop production, minimizing the need for fertilizer application (Deans et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigated groundwater is affected by high nitrate concentrations of non-anthropogenic origin (Stadler et al, 2008). Similar findings are known from other groundwater resources in semi-arid regions (Heaton et al, 1983;Barnes et al, 1992;Edmunds and Gaye, 1997;Deans et al, 2005). The aim of this study was to relate groundwater quality with indicators of recharge processes and groundwater residence time to gain insight into the time scale, conditions, and processes that control solute entry into groundwater.…”
Section: Introductionmentioning
confidence: 59%